Eustachian tube function of the infants with cleft palate - Endoh Chieko; Shinkawa Atsushi; Tanino Ryuzaburoh; Okubo Jin (Otology Japan, 1999)
It is well known that the middle ear diseases such as otitis media with effusion (OME) are very oftenly seen in those who have any anatomical anomaly and/or dysfunction of the Eustachian tube (E. T.).We investigated the gas-ventirating function of E. T. in cleft-palate-infants, with positive pressure loading test, which is one of the tests for evaluating E. T. ventilating function. We have also investigated the influence of palatinoplasty on E. T. ventilating function comparing the pre-and postoperative examination results.The subjects were 84 ears of 42 complete cleft-palate infants, and 25 ears of 13 incomplete cleft-palateinfants. Sixteen ears of 8 cleft-lip infants with normofunctional E. T. were adopted as a control group.We inserted a ventilation tube through the tympanic membrane before palatinoplasties, then both of passive tubo-opening pressure test and continuous endo-tympanic pressure test were performed before and after each operation.As a result, in passive tubo-opening pressure test, “closing failure pattern” was seen in 81.7%(89 of 109ears) of cleft-palate group, while the “normal pattern” was seen in 87.5%(14 of 16 ears) of the control group. In continuous endo-tympanic pressure measurement, “patulous tube pattern” was seen more frequently, and normal pattern was less frequently seen among the cleft-palate group than the control group.We concluded that E. T. of the cleft-palate-infant closes loosely and tends to open easily.There was no significant difference between pre-and postoperative examination results namely passive tubo-opening pressure test and continuous endo-tympanic pressure measurement (Mann Whitney U test and chai square statistics). So we considered that the palatinoplasty does not influenced to the ventilating function of E. T. at least in a short period of time.